PENGARUH PEMBERIAN Lactobacillus acidophilus TERHADAP pH DAN DAYA IKAT AIR DAGING BROILER - Mar’atus Solehah; RR Riyanti; Veronica Wanniatie; Dian Septinova (Department of Animal Husbandry, Faculty of Agriculture, University of Lampung, 2022)
This research aimed to (1) determine the effect of giving Lactobacillus acidophilus on pH and water holding capacity of broiler meat and (2) to determine the best concentration of Lactobacillus acidophilus on pH and water holding capacity of broiler meat. This research was carried out in September 2021 at the Animal Production Laboratory of the Animal Husbandry Department, University of Lampung and the Agricultural Product Technology Laboratory of Food Technology Department of the Lampung State Polytechnic. The research material used were 20 broiler chicken breast fillets. This study used a completely randomized design (CRD) with 4 treatments and 5 replications, namely without the addition of starter Lactobacillus acidophilus (P0), adding 5% starter Lactobacillus acidophilus (P1), adding 10% starter Lactobacillus acidophilus (P2), and adding 15% starter Lactobacillus acidophilus (P3). The observed variables were pH and water holding capacity. Data on pH and water holding capacity were analyzed using Analysis of Variance (ANOVA), and if the results obtained were significantly different, then followed by the Least Significant Difference Test (LSD). The results showed that the use of Lactobacillus acidophilus with concentrations of 5%, 10%, and 15% had a significant effect (P<0.05) on decreasing pH, but it had no significant effect (P>0.05) on water holding capacity. The best concentration of Lactobacillus acidophilus for pH value and water holding capacity was found in sample P3 with a concentration of 15% Lactobacillus acidophilus. Keywords: Lactobacillus acidophilus, preservation, pH, water holding capacity